Combined spinal-epidural for emergency cesarean section in a multiparous parturient with achondroplasia - Siyu Lye; Phui Sze Au Yong (Journal of Obstetric Anaesthesia and Critical Care, 2022)
Parturients with achondroplasia post unique challenges to the anesthetist. Term achondroplastic parturients may have cephalopelvic disproportion resulting in lower section cesarean section (LSCS). Premature ossification of bones results in characteristic craniofacial abnormalities and is associated with atlantoaxial instability and macroglossia leading to a difficult airway. With pregnancy, airway edema and reduced functional reserve capacity further complicate intubation. Central neuraxial blockade (CNB) is challenging due to potential kyphoscoliosis, spinal stenosis, the unpredictable spread of local anesthetics in central neural space, and uncertainty of dose due to disproportionate spinal column to overall height. We present the challenges in a multiparous achondroplastic parturient coming in for emergency cesarean section done under combined spinal-epidural anesthesia technique.